Capturing the dynamics of microbial interactions through individual-specific networks - Yousefi, Behnam; Melograna, Federico; Galazzo, Gianluca; van Best, Niels; Mommers, Monique; Penders, John; Schwikowski, Benno; Van Steen, Kristel (Frontiers in Microbiology, 2023)
Longitudinal analysis of multivariate individual-specific microbiome profiles over time or across conditions remains a daunting task. Most statistical tools and methods available to study microbiota are based on cross-sectional data. Over the past few years, several attempts have been made to model the dynamics of bacterial species over time or across conditions. However, the field needs novel views on incorporating individual-specific microbial associations in temporal analyses when focusing on microbial interactions. Here, we propose a novel data analysis framework called MNDA to uncover taxon neighbourhood dynamics that combines representation learning and individual-specific microbiome co-occurrence networks. We show that tracking local neighbourhood dynamics in microbiome interaction or co-occurrence networks can yield complementary information to standard approaches that only use microbial abundances or pairwise microbial interactions. We use cohort data on infants for whom microbiome data was available at 6 and 9 months after birth, as well as information on the mode of delivery and diet changes over time. In particular, MNDA-based prediction models outperform traditional prediction models based on individual-specific abundances and enable the detection of microbes whose neighbourhood dynamics are informative of clinical variables. We further show that similarity analyses of individuals based on microbial neighbourhood dynamics can be used to find subpopulations of individuals with potential relevance to clinical practice. The annotated source code for the MNDA framework can be downloaded from: https://github.com/H2020TranSYS/microbiome_dynamics. The MNDA workflow extracts information from matched microbiome profiles and opens new avenues to personalized prediction or stratified medicine with temporal microbiome data.